Breathable, moisture-absorbing and easy-to-rebound laminated composite nano polyester fiber and preparation method thereof
The laminated composite nanopolyester fiber is prepared through electrospinning technology. Combined with post-treatment technology, the problem of composite nanofibers being difficult to improve mechanical properties and wear resistance while improving breathability and softness, achieving multiple performance improvements of the fibers.
Patent Information
- Application Number
- CN202510030141.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing composite nanofibers are difficult to improve the mechanical properties and wear resistance of the fibers while improving breathability and softness.
Electrospinning technology is used to mix PET, DMF, PVP, graphene oxide, polymethyl methacrylate, polyurethane nanoparticles and nanocomposite particles to prepare a spinning liquid to form a spinning liquid to form a breathable, hygroscopic and easy to rebound stacked composite nanopolyester fiber, and the mechanical properties of the fiber are improved through post-treatment.
It improves the breathability, softness and mechanical properties of the fiber, enhances the wear resistance and antibacterial properties of the fiber, and optimizes the overall performance and production efficiency of the fiber.
Smart Images

Figure SMS_1 
Figure SMS_4 
Figure SMS_8
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fiber preparation, in particular to a laminated composite nano polyester fiber that is breathable, moisture-absorbent and easy to rebound. Background Art
[0002] Laminated composite nano polyester fiber is a high-performance nano fiber material with a specific structure prepared by electrospinning technology. It is widely used in medical health, air filtration, protective clothing, automobile manufacturing and other fields. Existing composite nano fibers are difficult to improve the mechanical properties and wear resistance of the fiber while improving the air permeability and softness.
[0003] The defects of existing nano polyester fiber preparation are: 1. Patent document CN110106635B discloses an ultra-short electrospun polyimide nanofiber and a preparation method thereof. It mainly considers how to prepare ultra-short nanofibers with uniform length distribution, but does not consider how to improve the mechanical properties and wear resistance of the fiber while improving air permeability and softness; 2. Patent document CN104480640B discloses a method and device for preparing nanofibers by air-blown parallel winding steel wire electrospinning. It mainly considers how to effectively improve the quality of polymer nanofiber nonwovens, but does not consider how to improve the production efficiency and quality of electrospinning. 3. Patent document CN110148726B discloses graphene-coated PAN-based ladder polymer ultrashort nanofibers and preparation methods and applications. It mainly considers how to form graphene-coated PAN-based ladder polymer nanofiber oriented tows, but does not consider optimizing the comprehensive performance of the fibers without affecting the mechanical properties of the nanofibers. 4. Patent document CN110184679B discloses an electrospun carbon hybrid polyimide ultrashort nanofiber and a preparation method thereof. It mainly considers how to obtain carbon hybrid polyimide ultrashort nanofibers with a small diameter, uniform fiber length and good dispersibility, but does not consider how to properly deal with the waste generated during the preparation to reduce resource waste. Summary of the invention
[0004] The purpose of the present invention is to provide a breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a breathable, moisture-absorbent and easily resilient laminated composite nano polyester fiber, wherein the raw materials thereof include the following components by weight: 12 to 24 parts of PET, 100 to 140 parts of DMF, 1 to 3 parts of PVP, 1 to 6 parts of graphene oxide, 5 to 11 parts of polymethyl methacrylate, 0.1 to 3 parts of polyurethane nanoparticles, 0.5 to 5 parts of a solution containing nanocomposite particles, and 0.1 to 2 parts of an antioxidant; PET, DMF, PVP, antioxidants, a solution containing nano-composite particles, graphene oxide, polymethyl methacrylate and polyurethane nanoparticles are mixed to prepare a spinning solution, which is then spun into laminated composite nano-polyester fibers using electrospinning technology.
[0006] Preferably, the solution containing nano-composite particles is prepared by mixing nano-titanium dioxide, nano-silicon dioxide, nano-zinc oxide and a silane coupling agent in a mass ratio of 1:(1-3):1:(3-12), and the particle size of the nano-composite particles ranges from 20 to 50 nm.
[0007] Preferably, the silane coupling agent is one or more of KH-560, KH-550 and KH-602.
[0008] Preferably, the antioxidant is one or more of antioxidant 168, antioxidant 1076, antioxidant 5057 and antioxidant DSTDP.
[0009] Preferably, the preparation method of the laminated composite nano polyester fiber is as follows: Step S1: Raw material preparation: pre-treating PET and performing surface modification treatment on nanocomposite particles and polyurethane nanoparticles; Step S2: Solution preparation: DMF is divided into two equal parts, and DMF is used to prepare a polymer solution and a precursor solution; Step S3: electrospinning: first, the polymer solution and precursor solution prepared in step S2 are loaded into the syringe of the electrospinning device, and two sets of multi-nozzle spinning devices are installed, wherein the inner diameter of the needle of the multi-nozzle spinning device is 0.2-0.4 mm, and then the power is turned on. Under the action of the high-voltage electrostatic field, the polymer solution and the precursor solution are ejected from the needles of the corresponding multi-nozzle spinning devices to form a jet, which is gradually refined and deposited on the receiving device under the action of the electric field force and volatilization, and is stacked layer by layer on the receiving device through a multi-nozzle method to form a laminated composite nano polyester fiber membrane; Step S4: post-processing: heat setting the laminated composite nano polyester fiber membrane prepared in step S3 to finally form a laminated composite nano polyester fiber; Step S5: Waste recycling and treatment: After the preparation is completed, the waste generated during the preparation process is uniformly collected; Step S6: Performance test: Perform a performance test on the laminated composite nano polyester fiber prepared in step S4.
[0010] Preferably, in step S1, the following steps are also included: Step S11: Pretreatment: placing the PET in an environment of 130-150° C. for 10-15 minutes for drying; Step S12: Surface modification: First, the silane coupling agent is stirred and diluted with a 75% ethanol aqueous solution, wherein the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1: (2-3), the stirring speed is 20-40 rpm, and the stirring time is 10-20 min to prepare a silane coupling agent solution, and the silane coupling agent solution is divided into three equal parts, namely solution A, solution B and solution C, respectively, and nano titanium dioxide, nano silicon dioxide and nano zinc oxide are added to the three solutions, and the three solutions are placed in a microwave reaction device, irradiated at a microwave frequency of 500-600 MHz for 10-20 min and a temperature of 120-160° C., and then the three solutions containing nanoparticles are mixed to obtain a solution containing nanocomposite particles.
[0011] Preferably, in step S2, the following steps are also included: Step S21: polymer solution preparation: PET is immersed in one portion of DMF, stirred at a speed of 60-80 rpm, wherein the heating temperature is 80° C., and the stirring time is 20-40 min, then PVP and antioxidant are added thereto, stirred at a speed of 70-90 rpm for 30 min under the condition of constant temperature to form a uniform polymer solution, then the prepared solution containing nanocomposite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion means to form a polymer solution; Step S22: Preparation of precursor solution: immerse graphene oxide and polymethyl methacrylate in another portion of DMF, and evenly disperse graphene oxide and polymethyl methacrylate in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160-170 rpm, the stirring time is 10-15 min, and the heating temperature is 60-120°C.
[0012] Preferably, in step S4, the following steps are also included: Step S41: pre-oxidation treatment: placing the laminated composite nano polyester fiber membrane obtained by electrospinning in a blast drying oven, raising the temperature to 260-280° C. at a heating rate of 2-3° C. / min, and keeping the temperature for 2-3 hours; Step S42: Carbonization treatment: Place the laminated composite nano polyester fiber membrane treated in step S41 into a vacuum crucible, introduce argon gas into the crucible, raise the temperature to 780-790° C. at a heating rate of 1° C. / min, and then keep the temperature for 2-4 hours; Step S43: functionalization treatment: soak the carbonized laminated composite nano polyester fiber in a positively charged polydimethyldiallyl ammonium chloride solution for 10 to 30 minutes and then wash it with deionized water. Then, soak the fiber in a negatively charged sodium polystyrene sulfonate solution for 10 to 30 minutes and then wash it again with deionized water. Repeat the above soaking and washing process 3 to 4 times. Step S44: finally, the treated laminated composite nano-polyester fiber is cleaned with thiourea dioxide solution at a water temperature of 20-30°C. After cleaning for 5-10 minutes, it is dried at a temperature of 40-60°C for 10-20 minutes.
[0013] Preferably, in step S5, the following steps are also included: Step S51: centrifuging the prepared waste liquid at a speed of 12000-13000 rpm for 10-30 min, and then discarding the supernatant to recover the nanoparticles; Step S52: first cut the fiber waste into small pieces of 5 to 10 cm in length, then put them into TFA to dissolve the fiber waste, wherein the temperature is 50°C, the stirring speed is 60 to 120 rpm, the stirring time is 30 to 45 min, and the impurities in the solution are filtered to obtain a spinnable solution, which is then spun using electrospinning technology.
[0014] Preferably, in step S6, the following steps are also included: Step S61: Perform an air permeability test according to GB / T5453-1997 "Test for Air Permeability of Textile Fabrics", test the weight change of the sample before and after being placed in a constant temperature and humidity environment at a temperature of 20°C and a relative humidity of 65%, and evaluate the moisture absorption performance, wherein the placement time is 24 hours, and use an electronic single yarn strength tester to test the fiber resilience; Step S62: Perform a tensile test according to GB / T14344-2008 "Test method for tensile properties of chemical fiber filaments" to evaluate the mechanical properties of the fiber.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The laminated composite nano polyester fiber prepared by the present invention retains the properties of the polyester fiber itself, such as being strong and durable, wrinkle-resistant and iron-free, not easy to get hair stuck, and easy to wash and dry quickly, and is also improved in terms of air permeability, softness, etc., thereby improving the wearing comfort to a certain extent. The structure of the nano fiber is improved by adding graphene, thereby improving the mechanical properties and wear resistance of the composite nano polyester fiber, and at the same time, the fiber prepared subsequently has certain antibacterial properties, thereby increasing the application range of the fiber. In addition, the laminated structure can further improve the mechanical properties of the nano fiber.
[0016] 2. The present invention optimizes the problem of graphene being prone to heavy stacking due to the action of van der Waals force through dual treatment with dispersants and physical methods, reduces the stacking problem to a certain extent, improves its dispersibility in the solution, and thus improves the preparation efficiency of the laminated composite nano-polyester fiber and the quality of the final product. In the electrospinning process, multiple nozzles are used for simultaneous spinning, which can increase the fiber output per unit time, prepare multiple layers of fibers at the same time, and thus improve the production efficiency of electrospinning.
[0017] 3. The present invention adds a certain proportion of nano-composite particles and polyurethane nano-particles during the preparation process, which not only enhances the moisture absorption, breathability and resilience of the fiber, but also gives the fiber a lasting antistatic effect and excellent ultraviolet absorption performance, which can effectively prevent the generation and accumulation of static electricity, reduce the harm of static electricity to the human body, effectively block the harm of ultraviolet rays to the human body, and improve the light aging resistance of fiber products, thereby extending the service life of fiber products. At the same time, it will not have a significant negative impact on the mechanical properties of nanofibers, thereby optimizing the comprehensive performance of the fiber.
[0018] 4. The present invention recycles waste, effectively improves the recycling and proper treatment of waste generated in the preparation process, reduces resource waste and environmental pollution, and reduces environmental pollution while ensuring the performance and preparation efficiency of the laminated composite nano polyester fiber. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The present invention provides a breathable, moisture-absorbent and easily resilient laminated composite nano-polyester fiber, and the preparation method of the laminated composite nano-polyester fiber is as follows: Step S1: raw material preparation: firstly, PET is placed in an environment of 130° C. for 15 minutes for drying treatment, and then the silane coupling agent is stirred and diluted with a 75% ethanol aqueous solution, wherein the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:2, the stirring speed is 40 rpm, and the stirring time is 15 minutes to prepare a silane coupling agent solution, and the silane coupling agent solution is divided into three equal parts, namely solution A, solution B and solution C, respectively, and nano titanium dioxide, nano silicon dioxide and nano zinc oxide are added to the three solutions, and the three solutions are placed in a microwave reaction device, irradiated at a microwave frequency of 550 MHz for 10 minutes, and the temperature is 140° C. Then, the three solutions containing nanoparticles are mixed to obtain a solution containing nano-composite particles, and the particle size of the nano-composite particles is 30 nm; Step S2: Solution preparation: DMF is divided into two parts, PET is immersed in one of the DMF parts, and stirred at a speed of 80 rpm, wherein the heating temperature is 80°C, and the stirring time is 30 minutes. Then PVP and antioxidant are added thereto, and stirred at a speed of 80 rpm for 30 minutes under the condition of constant temperature to form a uniform polymer solution, and then the prepared solution containing nanocomposite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion to form a polymer solution, and graphene oxide and polymethyl methacrylate are added thereto. Methyl acrylate is immersed in another portion of DMF, and graphene oxide and polymethyl methacrylate are uniformly dispersed in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160 rpm, the stirring time is 15 min, and the heating temperature is 80 ° C, wherein the mass ratio of PET, DMF, PVP, graphene oxide, polymethyl methacrylate, polyurethane nanoparticles, solution containing nanocomposite particles and antioxidant is (12-24): (100-140): 2: (1-6): 6: 1.2: (0.5-5): 0.5; Step S3: electrospinning: first, the polymer solution and precursor solution prepared in step S2 are loaded into the syringe of the electrospinning device, and two sets of multi-nozzle spinning devices are installed, wherein the inner diameter of the needle of the multi-nozzle spinning device is 0.3 mm, and then the power is turned on. Under the action of the high-voltage electrostatic field, the polymer solution and the precursor solution are ejected from the needles of the corresponding multi-nozzle spinning devices to form a jet, which is gradually refined and deposited on the receiving device under the action of the electric field force and volatilization, and is stacked layer by layer on the receiving device through a multi-nozzle method to form a laminated composite nano polyester fiber membrane; Step S4: post-treatment: placing the laminated composite nano polyester fiber membrane obtained by electrospinning in a blast drying oven, raising the temperature to 260°C at a heating rate of 2°C / min, and keeping it warm for 3 hours, then placing the laminated composite nano polyester fiber membrane treated in step S41 in a vacuum crucible, and introducing argon gas therein, raising the temperature to 780°C at a heating rate of 1°C / min, and then keeping it warm for 3 hours, then immersing the carbonized laminated composite nano polyester fiber after treatment in a positively charged polydimethyldiallylammonium chloride solution, and washing it with deionized water after soaking for 30 minutes, then immersing the fiber in a negatively charged sodium polystyrene sulfonate solution, and washing it again with deionized water after soaking for 20 minutes, and repeating the above immersion and washing process 4 times, finally washing the treated laminated composite nano polyester fiber with a thiourea dioxide solution, the washing water temperature is 30°C, and drying is performed after washing for 5 minutes, the drying temperature is 40°C, and the drying time is 15 minutes; Step S5: waste recycling: the prepared waste liquid is centrifuged at a speed of 12000 rpm for 25 min, and then the supernatant is poured out to recover the nanoparticles, and then the fiber waste is cut into small pieces of 10 cm in length, and then put into TFA to dissolve the fiber waste at a temperature of 50°C, a stirring speed of 100 rpm, and a stirring time of 40 min, and the impurities in the solution are filtered to obtain a spinnable solution, and then the electrospinning technology is used for spinning; Step S6: Performance test: Perform a performance test on the laminated composite nano polyester fiber prepared in step S4.
[0021] Further, the values in steps S2-S5 are changed, and steps S1 and S6-S8 are performed, and the prepared laminated composite nano polyester fiber is subjected to performance testing. The air permeability test is performed according to the standard GB / T5453-1997 "Test for Air Permeability of Textile Fabrics". The fiber sample is first placed in a drying oven at 105°C to a constant weight, and then the weight change of the sample before and after placement is detected in a constant temperature and humidity environment at a temperature of 20°C and a relative humidity of 65%, and the hygroscopic performance is evaluated. The placement time is 24h, and the formula is used for calculation:
[0022] Where W is the moisture regain, is the weight after drying, is the weight after 24 hours; Use an electronic single yarn strength tester to test the fiber's resilience. Fix one end of the sample on the instrument's fixture and apply a certain tensile force on the other end to make the fiber elongate by 30%. After maintaining for 30 seconds, remove the external force and record the fiber's rebound length within 60 seconds. The calculation formula is:
[0023] Where R is the rebound rate, is the original length, is the length after rebound, is the length after stretching; Step S62: Perform a tensile test according to GB / T14344-2008 "Test method for tensile properties of chemical fiber filaments" to evaluate the mechanical properties of the fiber.
[0024] Embodiment 1: Step S2: solution preparation: DMF is divided into two parts, PET is immersed in one of the DMF, and stirred at a speed of 80 rpm, wherein the heating temperature is 80° C., and the stirring time is 30 min. PVP and antioxidant are then added thereto, and stirred at a speed of 80 rpm for 30 min under the condition of constant temperature to form a uniform polymer solution, and then the prepared solution containing nanocomposite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion means to form a polymer solution, and graphene oxide and polymethyl methacrylate are immersed in another part of DMF, and graphene oxide and polymethyl methacrylate are uniformly dispersed in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160 rpm, the stirring time is 15 min, and the heating temperature is 80° C., wherein the mass ratio of PET, DMF, PVP, graphene oxide, polymethyl methacrylate, polyurethane nanoparticles, solution containing nanocomposite particles and antioxidant is 13:120:2:2:6:1.2:1.2:0.5.
[0025] Furthermore, the air permeability was measured to be 184L / m²·s, the moisture regain was 8.32%, the resilience was 86%, the tensile strength was 187MPa, and the elongation at break was 495%.
[0026] Embodiment 2: Step S2: solution preparation: DMF is divided into two parts, PET is immersed in one of the DMF, and stirred at a speed of 80 rpm, wherein the heating temperature is 80° C., and the stirring time is 30 min. PVP and antioxidant are then added thereto, and stirred at a speed of 80 rpm for 30 min under the condition of constant temperature to form a uniform polymer solution, and then the prepared solution containing nanocomposite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion means to form a polymer solution, and graphene oxide and polymethyl methacrylate are immersed in another part of DMF, and graphene oxide and polymethyl methacrylate are uniformly dispersed in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160 rpm, the stirring time is 15 min, and the heating temperature is 80° C., wherein the mass ratio of PET, DMF, PVP, graphene oxide, polymethyl methacrylate, polyurethane nanoparticles, solution containing nanocomposite particles and antioxidant is 19:120:2:3:6:1.2:2:0.5.
[0027] Furthermore, the air permeability was measured to be 217L / m²·s, the moisture regain was 8.54%, the resilience was 91%, the tensile strength was 256MPa, and the elongation at break was 553%.
[0028] Embodiment three: Step S2: solution preparation: DMF is divided into two parts, PET is immersed in one of the DMF, and stirred at a speed of 80 rpm, wherein the heating temperature is 80° C., and the stirring time is 30 min. PVP and antioxidant are then added thereto, and stirred at a speed of 80 rpm for 30 min under the condition of constant temperature to form a uniform polymer solution, and then the prepared solution containing nanocomposite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion means to form a polymer solution, and graphene oxide and polymethyl methacrylate are immersed in another part of DMF, and graphene oxide and polymethyl methacrylate are uniformly dispersed in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160 rpm, the stirring time is 15 min, and the heating temperature is 80° C., wherein the mass ratio of PET, DMF, PVP, graphene oxide, polymethyl methacrylate, polyurethane nanoparticles, solution containing nanocomposite particles and antioxidant is 22:110:2:3:6:1.2:2.5:0.5.
[0029] Furthermore, the air permeability was measured to be 262L / m²·s, the moisture regain was 9.46%, the resilience was 95%, the tensile strength was 281MPa, and the elongation at break was 612%.
[0030] Embodiment 4: Step S2: solution preparation: DMF is divided into two parts, PET is immersed in one of the DMF, and stirred at a speed of 80 rpm, wherein the heating temperature is 80° C., and the stirring time is 30 min. PVP and antioxidant are then added thereto, and stirred at a speed of 80 rpm for 30 min under the condition of constant temperature to form a uniform polymer solution, and then the prepared solution containing nano-composite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion to form a polymer solution, and graphene oxide and polymethyl methacrylate are immersed in another part of DMF, and graphene oxide and polymethyl methacrylate are uniformly dispersed in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160 rpm, the stirring time is 15 min, and the heating temperature is 80° C., wherein the mass ratio of PET, DMF, PVP, graphene oxide, polymethyl methacrylate, polyurethane nanoparticles, solution containing nano-composite particles and antioxidant is 21:130:2:2:6:1.2:2:0.5.
[0031] Furthermore, the air permeability was measured to be 233L / m²·s, the moisture regain was 9.18%, the resilience was 92%, the tensile strength was 263MPa, and the elongation at break was 561%.
[0032] Embodiment five: Step S2: solution preparation: DMF is divided into two parts, PET is immersed in one of the DMF, and stirred at a speed of 80 rpm, wherein the heating temperature is 80° C., and the stirring time is 30 min. PVP and antioxidant are then added thereto, and stirred at a speed of 80 rpm for 30 min under the condition of constant temperature to form a uniform polymer solution, and then the prepared solution containing nanocomposite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion means to form a polymer solution, and graphene oxide and polymethyl methacrylate are immersed in another part of DMF, and graphene oxide and polymethyl methacrylate are uniformly dispersed in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160 rpm, the stirring time is 15 min, and the heating temperature is 80° C., wherein the mass ratio of PET, DMF, PVP, graphene oxide, polymethyl methacrylate, polyurethane nanoparticles, solution containing nanocomposite particles and antioxidant is 13:100:2:2:6:1.2:1.1:0.5.
[0033] Furthermore, the air permeability was measured to be 95L / m²·s, the moisture regain was 8.71%, the resilience was 89%, the tensile strength was 220MPa, and the elongation at break was 529%.
[0034] The performance test results of laminated composite nano polyester fibers are as follows:
[0035] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber, characterized by: In terms of mass fractions, the raw materials include the following components: 12-24 parts of PET, 100-140 parts of DMF, 1-3 parts of PVP, 1-6 parts of graphene oxide, 5-11 parts of polymethyl methacrylate, 0.1-3 parts of polyurethane nanoparticles, 0.5-5 parts of a solution containing nanocomposite particles, and 0.1-2 parts of an antioxidant; PET, DMF, PVP, antioxidants, a solution containing nano-composite particles, graphene oxide, polymethyl methacrylate and polyurethane nanoparticles are mixed to prepare a spinning solution, which is then spun into laminated composite nano-polyester fibers using electrospinning technology.
2. The breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber according to claim 1, characterized in that: The solution containing nano-composite particles is prepared by mixing nano-titanium dioxide, nano-silicon dioxide, nano-zinc oxide and a silane coupling agent in a mass ratio of 1:(1-3):1:(3-12), and the particle size of the nano-composite particles ranges from 20 to 50 nm.
3. The breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber according to claim 2, characterized in that: The silane coupling agent is one or more of KH-560, KH-550 and KH-602.
4. The breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 168, antioxidant 1076, antioxidant 5057 and antioxidant DSTDP.
5. A method for preparing a breathable, moisture-absorbent and easily resilient laminated composite nano-polyester fiber, applicable to the breathable, moisture-absorbent and easily resilient laminated composite nano-polyester fiber according to claims 1-4, characterized in that: The preparation method of the laminated composite nano polyester fiber is as follows: Step S1: Raw material preparation: pre-treating PET and performing surface modification treatment on nanocomposite particles and polyurethane nanoparticles; Step S2: Solution preparation: DMF is divided into two equal parts, and DMF is used to prepare a polymer solution and a precursor solution; Step S3: electrospinning: first, the polymer solution and precursor solution prepared in step S2 are loaded into the syringe of the electrospinning device, and two sets of multi-nozzle spinning devices are installed, wherein the inner diameter of the needle of the multi-nozzle spinning device is 0.2-0.4 mm, and then the power is turned on. Under the action of the high-voltage electrostatic field, the polymer solution and the precursor solution are ejected from the needles of the corresponding multi-nozzle spinning devices to form a jet, which is gradually refined and deposited on the receiving device under the action of the electric field force and volatilization, and is stacked layer by layer on the receiving device through a multi-nozzle method to form a laminated composite nano polyester fiber membrane; Step S4: post-processing: heat setting the laminated composite nano polyester fiber membrane prepared in step S3 to finally form a laminated composite nano polyester fiber; Step S5: Waste recycling and treatment: After the preparation is completed, the waste generated during the preparation process is uniformly collected; Step S6: Performance test: Perform a performance test on the laminated composite nano polyester fiber prepared in step S4.
6. The method for preparing a breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber according to claim 5, characterized in that: In step S1, the following steps are also included: Step S11: Pretreatment: Place the PET in an environment of 130-150°C for 10-15 minutes for drying; Step S12: Surface modification: First, the silane coupling agent is stirred and diluted with a 75% ethanol aqueous solution, wherein the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1: (2-3), the stirring speed is 20-40 rpm, and the stirring time is 10-20 min to prepare a silane coupling agent solution, and the silane coupling agent solution is divided into three equal parts, namely solution A, solution B and solution C, respectively, and nano titanium dioxide, nano silicon dioxide and nano zinc oxide are added to the three solutions, and the three solutions are placed in a microwave reaction device, irradiated at a microwave frequency of 500-600 MHz for 10-20 min and a temperature of 120-160° C., and then the three solutions containing nanoparticles are mixed to obtain a solution containing nanocomposite particles.
7. The method for preparing a breathable, moisture-absorbent and easily resilient laminated composite nano polyester fiber according to claim 5, characterized in that: In step S2, the following steps are also included: Step S21: polymer solution preparation: PET is immersed in one portion of DMF, stirred at a speed of 60-80 rpm, wherein the heating temperature is 80° C., and the stirring time is 20-40 min, then PVP and antioxidant are added thereto, stirred at a speed of 70-90 rpm for 30 min under the condition of constant temperature to form a uniform polymer solution, then the prepared solution containing nanocomposite particles and polyurethane nanoparticles are added thereto, and dispersed by ultrasonic dispersion means to form a polymer solution; Step S22: Preparation of precursor solution: immerse graphene oxide and polymethyl methacrylate in another portion of DMF, and evenly disperse graphene oxide and polymethyl methacrylate in DMF by magnetic stirring to form a precursor solution, wherein the stirring speed is 160-170 rpm, the stirring time is 10-15 min, and the heating temperature is 60-120°C.
8. The method for preparing the breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber according to claim 5, characterized in that: In step S4, the following steps are also included: Step S41: pre-oxidation treatment: placing the laminated composite nano polyester fiber membrane obtained by electrospinning in a blast drying oven, raising the temperature to 260-280° C. at a heating rate of 2-3° C. / min, and keeping the temperature for 2-3 hours; Step S42: Carbonization treatment: Place the laminated composite nano polyester fiber membrane treated in step S41 into a vacuum crucible, introduce argon gas into the crucible, raise the temperature to 780-790° C. at a heating rate of 1° C. / min, and then keep the temperature for 2-4 hours; Step S43: functionalization treatment: soak the carbonized laminated composite nano polyester fiber in a positively charged polydimethyldiallyl ammonium chloride solution for 10 to 30 minutes and then wash it with deionized water. Then, soak the fiber in a negatively charged sodium polystyrene sulfonate solution for 10 to 30 minutes and then wash it again with deionized water. Repeat the above soaking and washing process 3 to 4 times. Step S44: finally, the treated laminated composite nano-polyester fiber is cleaned with thiourea dioxide solution at a water temperature of 20-30°C. After cleaning for 5-10 minutes, it is dried at a temperature of 40-60°C for 10-20 minutes.
9. The method for preparing the breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber according to claim 5, characterized in that: In step S5, the following steps are also included: Step S51: centrifuging the prepared waste liquid at a speed of 12000-13000 rpm for 10-30 min, and then discarding the supernatant to recover the nanoparticles; Step S52: first cut the fiber waste into small pieces of 5 to 10 cm in length, then put them into TFA to dissolve the fiber waste, wherein the temperature is 50°C, the stirring speed is 60 to 120 rpm, the stirring time is 30 to 45 min, and the impurities in the solution are filtered to obtain a spinnable solution, which is then spun using electrospinning technology.
10. The method for preparing the breathable, moisture-absorbent and resilient laminated composite nano-polyester fiber according to claim 5, characterized in that: In step S6, the following steps are also included: Step S61: Perform an air permeability test according to GB / T5453-1997 "Test for Air Permeability of Textile Fabrics", test the weight change of the sample before and after being placed in a constant temperature and humidity environment at a temperature of 20°C and a relative humidity of 65%, and evaluate the moisture absorption performance, wherein the placement time is 24 hours, and use an electronic single yarn strength tester to test the fiber resilience; Step S62: Perform a tensile test according to GB / T14344-2008 "Test method for tensile properties of chemical fiber filaments" to evaluate the mechanical properties of the fiber.
Citation Information
Patent Citations
A method and apparatus for preparing nanofibers by air-blown parallel spiral steel wire electrospinning.
CN104480640B
An ultrashort electrospun polyimide nanofiber and its preparation method
CN110106635B
Graphene-coated PAN-based ladder polymer ultrashort nanofibers, their preparation methods, and applications
CN110148726B
Electrospun carbon hybrid polyimide ultrashort nanofibers and their preparation method
CN110184679B
Polyelectrolyte nano-membrane-mediated terylene textile normal temperature normal pressure dyeing method
CN104911908A